Quality of Life with Late-Stage Dementia: Exploring Opportunities to Intervene - Ernecoff, Natalie C. (J Am Geriatr Soc, 2019)
BACKGROUND/OBJECTIVES. In late-stage dementia, families often prioritize quality of life (QoL) and comfort, yet little research examines factors impacting QoL. We sought to (1) describe temporal trends in QoL in late-stage dementia, and (2) explore associations between patient characteristics, care interventions, and QoL. DESIGN. Secondary analysis of data from the Goals of Care clinical trial SETTING. 22 nursing homes in North Carolina PARTICIPANTS. Family decision-makers for residents with late-stage dementia MEASUREMENTS. Family reported QoL at baseline and 9-months using the Alzheimer’s Disease-Related Quality of Life Instrument (ADRQL) with five subscales scored 0–100 (higher scores indicate better quality). Families reported demographics, primary goal of care, and described their perceptions of residents’ QoL. Chart reviews provided data on hospital transfers, treatment plans, and hospice enrollment. We ran mixed effects models of hypothesized variables and change in ADRQL over time. RESULTS. The study sample was 241 dyads of residents with late-stage dementia and family decision-makers. Family-reported ADRQL scores reflected moderately good QoL at baseline and 9 months (69.1 vs. 66.9; p=0.106). Subscales for Awareness of Self (62.8, GDS 5; 30.5, GDS 7; p>0.01) and Enjoyment of Activities (53.4, GDS 5; 39.4, GDS 7; p>0.01) were lower in later stage disease. Qualitatively, family associated better QoL for dementia with (1) activities, (2) opportunities to leave NH, (3) NH structured activities, (4) attentiveness in NH, and (5) passive interaction. ADRQL at nine months was associated with later dementia stage and referral to hospice (p<0.01). Age (p=0.004) and hospice enrollment were significantly associated with a larger decrease in ADRQL over 9-months (p=0.019). A primary goal of comfort was associated with a larger increase in ADRQL (p=0.022). CONCLUSION. Families judge QoL to be moderately good in late-stage dementia. They perceive activities, opportunities to leave the NH, and quality of interpersonal care as ways to improve dementia-specific QoL.